Occupational outcomes following mild traumatic brain injury in Canadian military personnel deployed in support of the mission in Afghanistan: a retrospective cohort study. Issue 5 (4th May 2016) - Garber, Bryan G; Rusu, Corneliu; Zamorski, Mark A; Boulos, David
Abstract : Objective: Deployment-related mild traumatic brain injury (MTBI) occurs in a significant number of military personnel but its long-term impacts are unclear. This study explores the impact of deployment-related MTBI on continued fitness-for-duty, with the ultimate intent of identifying potential targets for intervention to attenuate its effects. Participants: Consisted of 16 193 Canadian Armed Forces (CAF) personnel who deployed in support of the mission in Afghanistan and completed an enhanced postdeployment screening (EPDS) questionnaire over the period January 2009–July 2012. Primary outcome: The primary outcome was development of permanent medical unfitness defined as a 'career-limiting medical condition' (CL-MC). The secondary outcome was the diagnostic categories recorded for each individual at the time a CL-MC was established. Design: This study used a retrospective cohort design. Linked administrative and health data provided the primary outcome and the diagnoses responsible for it. Survival analysis was used to estimate the risk of a CL-MC and Cox regression provided adjusted HRs (aHRs) for the association between a CL-MC and MTBI, accounting for key covariates and confounders. Diagnostic categories associated with CL-MCs were identified. Results: Over a median follow-up period of 3.42 years, 6.57% of the study population developed a CL-MC. MTBI was independently associated with CL-MCs (aHR=1.65, 95% CI 1.35 to 2.03). Mental disorders and musculoskeletal conditions were the primary diagnoses associated with CL-MCs (identified as the primary diagnosis in 55.4% and 25.9%, respectively), and a neurological condition was only documented in 5.8% of those with MTBI who developed a CL-MC Conclusions: Deployment-related MTBI was associated with adverse occupational outcome but mental disorders and musculoskeletal conditions primarily drove subsequent medical unfitness. These findings support a diagnostic and treatment approach focusing on these comorbidities as the most promising strategy to minimise the burden of disability in MTBI-exposed military personnel.